Maternal Mid-Upper Arm Circumference as a Screening Tool to Predict Infant Birth Weight - Fathurrachman, Muhammad Rais; Umijati, Sri; Kurniawati, Eighty Mardiyan; Setyoboedi, Bagus (Folia Medica Indonesiana, 2023)
Highlights: 1. This study investigated the correlation between maternal mid-upper arm circumference and infant birth weight, aiming to present a different outcome compared to previous research. 2. The study's findings offer data suggesting that mid-upper arm circumference can serve as a screening tool for predicting infant birth weight. Abstract Mid-upper arm circumference (MUAC) is commonly used for assessing chronic energy deficiency in women of childbearing age. The measurement of MUAC during pregnancy mainly serves as early detection of potential low birth weight. However, certain studies have indicated no significant correlation between maternal MUAC and birth weight. Therefore, this study aimed to determine the relationship between maternal nutritional status and infant birth weight. The study used an analytical observational method with a cross-sectional approach, involving a sample of 86 mothers who delivered at Jagir Primary Healthcare Center in Surabaya, Indonesia, between July and December 2019. The participants were selected based on certain inclusion and exclusion criteria. The data were obtained from secondary sources, specifically the medical records of Jagir Primary Healthcare Center. The data were analyzed using the Spearman test, with a 95% confidence interval and a 5% margin of error. Most mothers (86.05%) had good nutritional status, as indicated by a MUAC measurement of â‰¥23.5 cm. Only 3.49% of infants were born with a low birth weight (<2,500 g), while 1.16% of infants were considered macrosomia (>4,000 g). Although most mothers exhibiting low MUAC did not give birth to infants with low birth weights, the analysis revealed a significant relationship (p=0.035) between maternal MUAC and infant birth weight. In conclusion, maternal MUAC can be utilized as a screening tool to predict infant birth weight because it indicates the condition of muscle tissue and subcutaneous fat, which serve as the mother's energy reserves. However, several variables can also impact infant birth weight, including maternal nutrient intake.